Personalized comprehensive rehabilitation program after surgical treatment of endometrial cancer: results of a prospective randomized comparative study - L. N. Sandzhieva; A. G. Solopova; D. V. Blinov; E. A. Son; V. N. Galkin; A. B. Alekseev (IRBIS LLC, 2022)
Aim: to evaluate effectiveness of a personalized comprehensive rehabilitation program in patients after surgical treatment of endometrial cancer (EC).Material and Methods. There were enrolled 61 patients of reproductive age (44.46 ± 3.84 years) after radical treatment of endometrioid adenocarcinoma by stratifying subjects into 2 groups: group I - «active» rehabilitation with a comprehensive program of restorative measures (n = 29), group II - «passive» rehabilitation with standard management of the postoperative period in accordance with volume and timeframe determined by clinical recommendations (n = 32). Quality of life (QоL) was determined using the following questionnaires: Functional Assessment of Cancer Therapy for Patients with Endometrial Cancer (FACT-En), Kupperman-Uvarova Modified Menopausal Index (MMI), The Female Sexual Function Index (FSFI), Hospital Anxiety and Depression Scale (HADS). The program was based on four patient visits expected to occur at week 1 as well as 3, 6, 12 months after surgery, respectively.Results. In was found that 12 months post-surgery MMI in group I was decreased from 40.75 ± 5.69 down to 26.45 ± 4.84 score corresponding to mild postovariectomy syndrome (POES), whereas in group II - from 39.62 ± 5.37 to 36.15 ± 4.06 score estimated as moderate POES. In addition, at this time point patients in group I were noted to virtually fully recover sexual function assessed by FSFI (24.93 ± 2.86 score), whereas in group II it was at markedly lower level (13.39 ± 2.55 score; p < 0.001). According to the HADS, all subjects had level exceeding score of 11 at week 1 post-surgery corresponding to clinically significant anxiety and depression. Moreover, 6- and 12-months post-surgery subjects in group I lacked significant symptoms (score < 7 for each parameter), whereas in group II 12-month follow-up demonstrated subclinical level of anxiety and depression. According to the FACT-En, subjects in group I vs. group II revealed markedly higher QoL on visit 4 reaching 141.31 ± 6.45 and 112.84 ± 6.48 score, respectively.Conclusion. The «active» personalized comprehensive rehabilitation program proposed here demonstrated high efficacy in EC patients after radical surgery compared to subjects underwent standard management in rehabilitation period. Use of the program during 12 months post-surgery allowed to minimize negative manifestations related to POES, positively impacted psycho-emotional status, significantly improved sexual function as well as QoL. Organizing comprehensive rehabilitation in post-surgical EC patients should be considered as one of high-priority approaches in public healthcare.